Exploring Learners' Expectations of Sustainability Objectives and Organizational Change: The Case of Gender Reporting Training - Oppi, Chiara (Frontiers in Sustainable Cities, 2021)
Sustainability reporting (SR) practices at higher education institutions (HEIs) appear fragmented and underutilized. Research is needed to persuade HEIs to adopt SR standards, explaining the SR advantages of achieving sustainability objectives and realizing organizational change. Only a few research studies have investigated how HEIs employees can be trained on SR and how this can affect SR implementation. This research explores SR training for HEIs employees, focusing on gender reporting (GR) training as a means to achieve sustainability objectives and realize organizational change. Among the United Nations’ Sustainable and Development Goals (SDGs), gender equality emerges as a relevant topic to investigate, also in the HEIs context, with current research being limited. Through a survey among Italian HEIs employees who attended a GR training course, this study investigates the effects of learning outcomes of respondents’ expected achievement of GR objectives and organizational change after GR implementation. The research also studies whether the perceived organizational barriers to GR affect the expected realization of organizational change. The results support the impact of learning outcomes on the expected achievement of GR objectives and organizational change. Conversely, the perceived organizational barriers to GR do not affect the expected realization of organizational change. The study enters the debate about GR at HEIs and contributes to literature on sustainability training for HEIs employees, providing practical implications for organizations that intend to implement such training and showing their advantages.